A survey of epiphytic organisms in cultured kelp Saccharina japonica in Korea. Issue 1 (December 2017) - Kim, Jong-Oh; Kim, Wi-Sik; Jeong, Ha-Na; Choi, Sung-Je; Seo, Jung-Soo; Park, Myoung-Ae; Oh, Myung-Joo
Abstract A survey was conducted to investigate the presence of epiphytic organisms in four kelpSaccharina japonica farms in the coastal area of Korea from 2014 to 2015. Of 740 kelp samples that were taken, 208 exhibited six kinds of epiphytic organisms, including hydroid (detection rate: 11.6%), bryozoan (6.4%), polychaete (3.4%), algae (3.2%), caprellid (3%), and oyster (0.5%). The infestation rate for hydroid, bryozoan, and polychaete was significantly higher in the Wando farm, Busan farm, and Pohang farm, respectively. Epiphytic organisms were generally observed during May to September and not January to April, indicating that their infestation was significantly higher when the water had a higher temperature. The histopathogical examination revealed that hydroid and bryozoan organisms were attached on the cuticula of the thallus while some algae were attached on the cuticula of the thallus or had penetrated the epidermis. These results indicate that hydroid and bryozoan were the most predominant epiphytic organisms in Korean kelp farms, even though the infested thallus had not been broken.